The Language Landscape: Exploring English Proficiency of Vocational University Students through TOEIC Simulation - Mochammad Abdullah Salim; Ummy Khoirunisya Masyhudianti (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study explores the English proficiency levels of vocational university students majoring in Mechanical Engineering, assessed through a TOEIC simulation test. Seventy-four students participated in the study, which used a modified TOEIC test with 18 representative questions due to time constraints and students' unfamiliarity with the full test format. The results indicated a mean score of 53.38 out of 100, with a significant range from 15 to 90, highlighting substantial variability in proficiency levels. The majority of male students scored higher than female students, suggesting potential gender-related differences in language acquisition within this cohort. A positive correlation was found between students' TOEIC scores and their academic performance in Mechanical Engineering courses, underscoring the importance of English proficiency for academic success. The discussion contextualizes these findings within second language acquisition theories and compares them with previous studies, emphasizing the necessity for targeted English language support tailored to vocational students' needs. Practical recommendations include integrating specialized English training into the vocational curriculum, offering supplemental language support, and implementing regular language proficiency assessments. The study's implications for policy and practice highlight the need for enhanced language instruction to improve vocational students' academic and professional outcomes.